Análisis estadístico comparativo del contenido de óxidos presentes en lodos sin calcinar, lodos calcinados y cemento portland (2019)
In this research work, the quantities of oxides present in sludge coming from drinking water treatment plant in Barranquilla, Colombia was determined; part of specimen (2.0 kg) was calcined at 800 °C and the other portion was dried during three days with surrounding temperature. The concentration of oxide in sludge calcined and sludge not calcined was get by X-rays fluorescence, the results were validated by ASTM C114, to compare the results with oxides concentration in Portland cement type I. Statistically it was revealed there is a significant ifference in calcium oxide, silicon dioxide, ferric oxides and aluminum oxide concentrations of the sludge and the Portland cement. The sludge coming from drinking water treatment plant have a high cementitious potential when classified as a class F pozzolan with low calcium oxide content, in accordance with ASTM C618. The percentages of magnesium oxide and sulfur rioxide in the sludge don’t exceed the values required by the ASTM C150 standard